Animasi Edukasi Konsumen Tentang Manfaat Gula Semut Menggunakan Motion Graphic - Akhmad Yusuf Fauzi; Rahman Rosyidi; Hendra Marcos (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2021)
Consumer education animation is a media to provide education to consumers, so that consumers are affected so that consumers do what is expected of education practitioners. Consumer education is carried out because in Indonesia there are still many who do not know the dangers of consuming sugar which can lead to diabetes mellitus.  The method used is MDLC (Multimedia development Life Cycle) which consists of six stages, namely, concept, design, material collection, manufacturing, testing, and distribution. Making consumer education animations using Adobe After Effects cc 2015, designs are made as attractive as possible and display data clearly. The results of this study in the form of Consumer Education Animation Video about the Benefits of Ant Sugar Using Motion Graphic. In addition, the results of respondents' testing in this study showed that "Consumer Education Animation About the Benefits of Ant Sugar" has a value of an average of 86% of 20 respondents, so it is included in the category of very much agree, because with the value of these numbers it can be interpreted as an Educational Animation Video Consumers About the Benefits of Ant Sugar is able to provide education to the public that ant sugar is the right choice to switch from granulated sugar because ant sugar contains a number of advantages and benefits that are good for consumption.